Financial repression and economic distortions to the stage of economic growth and agricultural development in Bangladesh (Journal of the Bangladesh Agricultural University, 2010)
Financial repression in a developing country is not new to us. The government may take policy for financial repression due to easy collection of inflation tax to the stage of economic development. This study is concerned to find the positive relationship between financial development and economic growth and productivity in the economy of Bangladesh. The research concluded that the financial repression has a negative relationship to the economic growth and productivity but the financial development is positively to relate the economic growth and productivity in the economy of Bangladesh. This study found evidence that the effect of financial repression is positive to the financial development in Bangladesh as it was to the high growth period in Japan. But the scenario was different for Latin American countries. Transition to the financial development from the stage of financial repression to the stage of financial liberalization is found positive to the economic growth and productivity in Bangladesh. The rural finance in agro sector is statistically significant at the level of 5% in two tail test and contributing financial sector development where the urban finance is still suffering various economic distortions to the economic growth and productivity. Keywords: Financial Repression; Economic Distortion; Sustainable Economic Growth DOI: 10.3329/jbau.v6i2.4845 J. Bangladesh Agril. Univ. 6(2): 437-448, 2008